"Cos he's my favourite character!" A children's rights approach to the use of popular culture in teaching literacy. (20th February 2014) - Dunn, Jill; Niens, Ulrike; McMillan, Dorothy
Abstract The current educational climate of concern for children's achievement in literacy has resulted in a plethora of policies aimed at raising standards. Considerable research has been carried out in the field of popular culture and its potential for motivating and engaging children in literacy learning. However, there has been little research on children's views on this issue. This study was influenced both by the changing perceptions of childhood and by Article 12 of the United Nations Convention on the Rights of the Child. A variety of participatory methods was used to gather views from children and a Children's Research Advisory Group was also asked to assist with developing the research methods and interpreting the data. The results show that when children are given a choice, popular culture features strongly in what they would like to write about. All children demonstrated their diverse knowledge and enjoyment of a wide range of popular culture. This small‐scale study provides valuable insights into children's views on the use of popular culture for the teaching of writing and raises challenging questions for policy and practice in the continuous quest for a meaningful curriculum for contemporary children, which will ultimately raise standards in literacy.